Kontribusi Pembelajaran PAI terhadap Pemahaman Siswa tentang Kesehatan Mental: Studi di Sekolah Menengah Pertama - Dia Elkomariah (PT. Willy Print Art, 2025)
This study aims to examine the contribution of Islamic Religious Education (PAI) learning to students' understanding of mental health at the junior high school (SMP) level. The background of this research is based on the growing awareness of the importance of mental health among adolescents, as well as the strategic role of PAI in shaping character and spiritual values that can support mental well-being. This research uses a qualitative approach with a case study method, where data were collected through observation, interviews, and documentation at one selected junior high school. The results of the study show that PAI learning provides a positive contribution to students' understanding of mental health, particularly through moral education materials, the exemplary behavior of teachers, and religious discussions that encourage students to better understand themselves, manage their emotions, and build healthy social relationships. Thus, PAI learning can serve as a preventive approach in supporting students' mental health from an early age.